Federal Court Cases: Integrated Data Base, 2012 ([Verlag nicht ermittelbar], 2014)
The purpose of this data collection is to provide an official public record of the business of the federal courts. The data originate from district and appellate court offices throughout the United States. Information was obtained at two points in the life of appellate and civil cases: filing and termination. The termination data (archived in this data collection) contain information on both filing and terminations, while the pending data (archived as a separate data collection) contain only filing information on the most recent pending cases. The unit of analysis for the appellate and civil terminations data is the case. This collection also contains data on criminal cases in federal courts. However, the unit of analysis for the criminal data is the defendant, and a defendant can be included in several cases.